New records of the Western Rounded Ear Bat, Lophostoma occidentalis (Davis & Carter, 1978) (Chiroptera: Phyllostomidae), from Colombia (2015)
We report new records of the western rounded ear bat Lophostoma occidentalis for the Colombian territory, rep-resented by ten specimens collected on the western portion of the country, in the departments of Cauca, Chocó, and Valle del Cauca, all in the Colombian Pacific Region. The new re-cords of L. occidentalis represent a substantial geographic and ecological extension in the known distribution of this species and corroborate its occurrence in Colombia. In addition, we discuss on the morphological variation of representatives of large Lophostoma species in Colombia.